A Peran Zakat dalam Mengurangi Kesmikinan: Peran Zakat dalam Mengurangi Kesmikinan - Qurrotul Millah; adinda adinda (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2022)
This article describes the role of zakat in poverty alleviation. Education in the obligation of zakat can be gleaned from curiosity to give, berinfak and give up some of its property as evidence of compassion for fellow human beings. In the social field, the charity, the poor group can play a role in his life, acted upon its obligations to God, for helping zakat and sadaqah given by people who are able. With the zakat Similarly, people who are not able to feel that they are part of the community members, not the wasted and underestimated. In the economic field, zakat can play a role in preventing the accumulation of wealth in a few hands only, and obliges the rich to redistribute wealth to the group of the family fortune and destitute. So, zakat also serve as a potential source of funds for poverty reduction. Zakat can also serve as working capital for the poor to be able to open up employment opportunities, so they can earn and be able to meet their daily needs harinya.ipetik of curiosity giving, berinfak and give up some of its property as evidence of compassion for fellow human beings. In the social field, the charity, the poor group can play a role in his life, acted upon its obligations to God, for helping zakat and sadaqah given by people who are able.